Development, Implementation and Evaluation of a Multi-ethnic Peer Education Programme for the Prevention of Sexually Transmissible Infections and HIV among University Students in Northwest China - Walkingshaw, John (Curtin University, 2019)
This thesis describes the development of linguistically (first language) and culturally acceptable teaching materials that were employed in an HIV/STI prevention peer education programme targeting the four predominant ethnic groups (Han, Hui, Mongolian and Tibetan) at a university for nationalities in Northwest China. A 39 item questionnaire (HIV/STI-KQ-39) was also developed to assess participants’ knowledge. There was a statistically significant increase in knowledge level between pre- and post-intervention in three of the four ethnic groups.